Efficacy and impact of sanitizers in controlling pathogenic bacteria on irrigation water - Santillan Oleas, Valeria Paola, author; Gutierrez-Rodriguez, Eduardo, advisor; Geornaras, Gina, committee member; Uchanski, Mark, committee member; Ma, Jianbing, committee member (Colorado State University. Libraries, 2024)
Irrigation water quality is crucial for fresh produce. However, the absence of practical microbial water standards and EPA-registered sanitizers poses challenges for growers, impacting food security and increasing the risk of foodborne outbreaks. This study compared the effectiveness of commercial sanitizers (sodium hypochlorite - Chlo, peroxyacetic acid - PAA) and novel chemistries (sodium acid sulfate - SAS, potassium acid sulfate - KAS) at different concentrations for achieving a 3-log reduction of E. coli O157:H7 (EHEC), Salmonella (SM), or Listeria monocytogenes (LM). Additionally, the study examined their corrosive effects on aluminum and stainless steel, as well as their impact on plant and soil chemical and physical properties. Sanitizer evaluations were conducted under varying turbidities (0, 50, 100, 150 NTU), contact times (CT: 3 or 5 minutes), and bacterial concentrations of EHEC, SM, or LM at 6 and 3 log CFU/mL per EPA 2020 guidelines. Treatments that achieved a 3-log reduction of the selected organisms within a 5-minute contact time, with no viable cells after enrichment, were considered the most effective and exceeded EPA requirements. These treatments were then evaluated for their corrosion capacity on stainless steel (SS304, SS316) and aluminum (AL3004) coupons, as well as their effects on soil and plant health (romaine lettuce) under greenhouse conditions. Chlo at 60 ppm, SAS at 0.60%, and PAA at 30 ppm achieved a 3-log reduction, with no viable cells after enrichment, for all strains after a 5-minute contact time (P<0.05). The corrosion capacity for the most effective treatments was tested at 14-day intervals at 23°C and 73°C for stainless steel (SS304, SS316) and aluminum (AL3004) coupons submerged in each sanitizer solution. There was no significant difference in corrosion between SS304 and SS316 (P<0.05). AL3004 showed greater corrosion than SS, with the highest rate observed at 0.6% SAS (4.52E-02 cm/year). Greenhouse-grown romaine lettuce was spray-inoculated with a bacterial cocktail of LM/EHEC at 5 log CFU/mL. Bacterial recovery was performed at 0-, 4-, 8-, and 12-days post-inoculation using selective-differential media. Soil samples were collected from treated and non-treated samples to assess soil chemical and physical properties. Bacterial inactivation had a negative correlation with water turbidity and a positive correlation with contact time and sanitizer concentration (P<0.05). In the greenhouse trial PAA, Chlorine and SAS exhibited a higher bacterial reduction compared to a water-control, with marginal differences in reduction between sanitizers (P<0.05). The highest reduction was achieved by PAA (0.98 log CFU/gram-lettuce) reduction compared to the water control. SAS exhibited phytotoxicity in the lettuce leaves in the second greenhouse trial. All sanitizers caused marginal changes in the overall properties of soil physical and chemical properties, with sodium and electrical conductivity being the main factors affected by the constant application of each sanitizer.
Keywords: corrosion; sanitizers; plant - soil health; bacterial reduction